CAR-T Cell Therapy for Acute Myeloid Leukemia: Where Do We Stand Now? - Pilar Lloret-Madrid; Pedro Chorão; Manuel Guerreiro; Pau Montesinos (Current Oncology)
Background: Patients with refractory and relapsed acute myeloid leukemia (R/R AML) face a dismal prognosis. CAR-T therapy has emerged as a potential treatment option. This study assesses the available clinical evidence on CAR-T in R/R AML, focusing on safety and efficacy outcomes. Methods: We included studies on CAR-T therapy for R/R AML published from June 2014 to January 2025. Data on patient and disease characteristics, CAR-T constructs, response rates, post-CAR-T allogeneic HSCT (allo-HSCT), and safety outcomes were analyzed. Results: Twenty-five CAR-T clinical trials involving 296 patients were identified. The most frequently targeted antigens were CD33, CD123, and CLL-1, while CD7, CD19, NKG2D, and CD38 were also explored. Responses were heterogeneous and often short-lived when not consolidated with allo-HSCT. Cytokine release syndrome and neurotoxicity were generally low grade and manageable. Prolonged and severe myelosuppression was a frequent limiting toxicity, often requiring allo-HSCT to restore hematopoiesis. Disease progression was the leading cause of death, followed by infections. Conclusions: CAR-T cell therapy may represent a feasible therapeutic strategy, particularly as bridging to allo-HSCT to mitigate myelotoxicity and improve long-term outcomes. Nevertheless, it remains in the early stages of development and faces significant efficacy and safety challenges that must be addressed in future trials to enable the expansion of this promising therapeutic approach for a population with high unmet medical needs.